De la épica a la sátira: cimarrones y esclavos en la literatura colonial del Perú (Miramontes y El Ciego de la Merced) - de Navascués, Javier (Verbum – Analecta Neolatina, 2021)
The projection of the Subject in the Other tells us much about the Subject himself and his means of being and understanding the world. The representation of two communities – the Maroons (“Cimarrones”) of the Isthmus of Panama, and the Afro-descendants of Lima – reveals how their images were built upon the crossing of certain literary conventions and the colonial political system. This article analyses a 17th Century epic poem, Armas Antárticas (Antarctic Weapons), by Juan de Miramontes, and the satirical poetry of Francisco del Castillo, also known as “El Ciego de la Merced” (18th Century). Miramontes is inspired by certain conventions of the literary epic and, as a consequence, configures an idealized representation of the enemy, which in this case is the “Cimarrón” (i.e., a rebellious and fugitive slave). In contrast, the satirical representation of the Afro-descendant by del Castillo is absolutely denigrating, in accordance with the Hispanic tradition of the literary genre itself. However, in both cases, negros, mulatos and zambos libres are represented as a threat to the colonial system.